Constraint Based Syntax of Modifiers - Loukanova, R. (2011 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology, 2011)
The paper introduces a technique for grammar rules that licence post-and pre-modified phrases, by using a generalized approach to constraint based lexicalized grammar. The rules generate iterative modification by avoiding spurious syntactic ambiguity. The rules of syntactic modification are lexically restricted by the lexical head of the modifier expression via a grammatical feature and its value.